Elemen Listening Sebagai Soft Power: Diplomasi Publik Arab Saudi Melalui Pagelaran Riyadh Masters - Ario Bimo Utomo; Baswedan, Zaidan Muhammad (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2025)
This article is composed to examine the discussion regarding how Saudi Arabia utilizes the Riyadh Masters Event as an instrument of public diplomacy, with a focus on Nicholas J. Cull’s taxonomy—specifically the “listening” function. Citing Cull’s concept, he argues that listening is the most analytically suitable framework for understanding the engagement of government–in this case through the regime of de facto Mohammed bin Salman–through early-stage with the global esports community, particularly under its Vision 2030 agenda. The research is based on a qualitative analysis of online discourse, stakeholder actions, and official communication. Data were collected through digital ethnography and content analysis across Reddit, Twitter, and tournament coverage. Findings suggest that Saudi Arabia employs esports not only for entertainment or economic diversification but as a way to monitor global sentiment, assess international reputation, and align its diplomatic narrative. The centralized public diplomacy model in Saudi Arabia enables coordinated listening practices, with implications for future cultural and digital diplomacy efforts. Ultimately, this article contributes to a growing body of literature that explores digital platforms, gaming culture, and international engagement from a Global perspective. Keywords: Public Diplomacy, Esports, Saudi Arabia, Listening, Soft Power